2021
DOI: 10.1097/inf.0000000000003417
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Staphylococcus Aureus Endocarditis Misdiagnosed as Multisystem Inflammatory Syndrome in Children

Abstract: We present a case of a 10-year-old male with Staphylococcus aureus mitral endocarditis who was initially misdiagnosed with multisystem inflammatory syndrome associated with coronavirus disease 2019, with eventual fatal outcome due to brain hemorrhage after cardiac intervention. Our case differs from recent studies, in which microbleeds did not increase the risk of hemorrhagic stroke or global mortality risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…We found a recent case report of a previously healthy 10‐year‐old with fatal S. aureus infective endocarditis, which was clinically compatible with MIS‐C 7 . The use of intravenous immunoglobulin, glucocorticoids and biologic agents for the treatment of MIS‐C is currently not standardised and they are recommended based on clinical presentation 2 .…”
Section: Discussionmentioning
confidence: 99%
“…We found a recent case report of a previously healthy 10‐year‐old with fatal S. aureus infective endocarditis, which was clinically compatible with MIS‐C 7 . The use of intravenous immunoglobulin, glucocorticoids and biologic agents for the treatment of MIS‐C is currently not standardised and they are recommended based on clinical presentation 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the SARS-CoV-2 reverse transcription polymerase chain reaction and serology results were ultimately negative, MIS-C was initially suspected as the cause of the patient’s symptoms. Subsequent, echocardiography showed that the mitral valve had an echogenic lesion, and blood culture results turned positive for Staphilococcus aureus sensitive to methicillin ( Peña-Moreno et al., 2022 ).…”
Section: Endocarditis In Children With Covid-19 Infectionmentioning
confidence: 99%